L’étonnement : un vecteur didactique en formation professionnelle - Joris Thievenaz; Thierry Piot (Recherches en Éducation)
While in philosophy the astonishment approach has always considered prior to any act of thought and production of new knowledge, the concept curiously remains outside the field of education and training. We show in this paper how the "encouragement and support the astonishment" is a powerful didactic lever to encourage the occurrence of new learning in the learner. This is to study more specifically the concrete uses arising from this notion. For this, we record our reflection in a pragmatic approach of experience (Dewey, 1938) and support our remarks on case studies from support systems of student interns at the moment of debriefing of interns return in the Nursing Care Training Institute.